A flexible middleware for multimedia communication design, implementation, and experience. - Stiller, B.
Distributed multimedia applications require a variety of communication services. These services and different application requirements have to be provided and supported within: (1) end-systems in an efficient and integrated manner, combining the precise specification of quality-of-service (QoS) requirements, application interfaces, multicast support, and security features and (2) the network. The Da CaPo++ system presented in this paper provides an efficient end-system middleware for multimedia applications, capable of handling various types of applications in a modular fashion. Application needs and communication demands are specified by values in terms of QoS attributes and functional properties, such as encryption requirements or multicast support. Da CaPo++ automatically configures suitable communication protocols, provides for an efficient runtime support, and offers an easy-to-use, object-oriented application programming interface. While its applicability to real-life applications was shown by prototype implementations, performance evaluations have been carried out yielding practical experiences and numerical results
Keywords: Da CaPo++ system; QoS; Communication protocols; Communication services; Distributed multimedia applications; Efficient runtime support; Encryption requirements; End-system middleware; Flexible middleware; Multicast support; Multimedia communication; Object-oriented application programming interface; Performance evaluations; Picture phone; Quality-of-service.; Real-life applications; Security features